Investigating the dynamics of the profit rate, the exchange rate, and terms of trade in Brazil - Marquetti, Adalmir Antonio; Miebach, Alessandro; Morrone, Henrique; Volkweis Leite, Samuel (PSL Quarterly Review, 2025)
This paper explores the intricate relationship between profit rates, exchange rates, and terms of trade in the Brazilian economy from 2000 to 2023. Building on Weisskopf’s (1979) decomposition of the profit rate, we demonstrate how exchange rates and terms of trade affect profit share, the potential output-capital ratio, and capacity utilization. Our results reveal a nonlinear, U-shaped relationship between exchange rates and profit rates. While currency devaluation can boost profit rates by increasing the profit share, it may negatively affect the potential output-capital ratio. Conversely, currency appreciation can raise the potential output-capital ratio but reduce the profit share. We show that terms of trade play a key role in shaping profit rates. Improvements in terms of trade can elevate the profit share, the potential output-capital ratio, and capacity utilization, leading to higher profitability. However, the impact of terms of trade on profit rates is complex, as they also influence exchange rates. Our findings underscore the importance of understanding the dynamic interplay between exchange rate, terms of trade, and the profit rate for economists and policymakers.